A Systematic Review of Cross-Cultural Adaptation of the Neck Disability Index. Issue 7 (1st April 2015) - Yao, Min; Sun, Yue-li; Cao, Zuo-yuan; Dun, Rong-liang; Yang, Long; Zhang, Bi-meng; Jiang, Hui-ru; Wang, Yong-jun; Cui, Xue-jun
<x xml:space="preserve">Abstract</x> Study Design. Systematic review of cross-cultural adaptation. Objective. To perform a systematic review of cross-cultural adaptations of the Neck Disability Index (NDI) and to give a critical assessment to improve its translation. Summary of Background Data. The NDI is used to assess functional capacity and physical activity in patients with neck pain, but the quality of its cross-cultural adaptations has not been systematically reviewed. Methods. PubMed, Cochrane Library, and EMBASE were searched up through 2013 to identify studies of cross-cultural NDI adaptations. Search terms were "Neck Disability Index" or "NDI" and "cross-cultur*" or "cultur*" or "valid*" or "equivalence" or "transl*." Data were extracted and study quality was assessed. Results. Twenty-four different NDI versions were identified from 14 different languages/cultures. Most reported forward and back translation and pretesting, but sample size was a problem for most studies. The Cronbach α was generally acceptable, and 13 versions met the criterion of reliability by reporting an intraclass correlation coefficient of 0.70 or more, although some versions did not reach the minimal intraclass correlation coefficient. Eleven versions tested ceiling and floor effects, but only 1 Japanese version reported a floor effect. No study reported interpretability, and none provided the minimal important change or minimal important difference. Conclusion. The Arabic, Italian, and Thai versions were of higher quality than the other versions according to the overall assessment of the 3 checklists. The Catalan, Chinese, Japanese, Korean, Thai, and Turkish versions need more research according to the Quality Criteria for Psychometric Properties of Health Status Questionnaire. Pretest sample size was not large enough in most cases. Level of Evidence: 1